LOYIHA BOSHQARUVI UCHUN RAQAMLI VOSITALAR: TENDENSIYALAR VA LOYIHA MUVAFFAQIYATIGA TA‘SIRI - Djurayev Akmal Mamatovich, (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
The development of digital technologies is one of the main trends in the development of the world economy. The emergence and spread of digital manufacturing technologies are increasingly blurring the lines between physical and digital manufacturing systems. Analysis of the dynamics of investments in research and development in various technological areas showed the maximum growth of investments in areas related to the introduction of digital technologies. The purpose of the research is to research and develop mathematical models that include the development of theoretical rules and methodological and instrumental tools for the flexible management of digital innovation projects in the context of the dynamically changing external and internal environment of the organization in the project activity..